Utilization patterns and satisfaction levels among beneficiaries attending Ayushman Bharat health and wellness centres in a coastal district of Tamil Nadu, India - Sivakumar, Abinav; Boratne, Abhijit V.; Chellamuthu, Lalithambigai; Venkataraman, Surendran (International Journal Of Community Medicine And Public Health, 2024)
Background: “Ayushman Bharat” has its twin pillars of health and wellness centers (HWCs) and “Pradhan Mantri Jan Arogya Yojana” which looks at health holistically and lays significant milestone towards India’s path to universal health coverage. To ensure delivery of comprehensive primary health care, existing sub health centres and certain primary health centres were transformed to HWCs. Objectives were to assess the utilization patterns and measure the satisfaction levels among beneficiaries attending Health and Wellness Centres in rural and urban areas of Cuddalore district, Tamil Nadu, India. Methods: A cross-sectional study was undertaken over a period of six months among 808 beneficiaries from eight of the newly upgraded HWCs of Cuddalore. A multi-stage stratified cluster sampling was employed. Data was collected by exit interviews using semi-structured questionnaire. Data entry and analysis was done by Epidata 3.1 and SPSS 21. Results: Majority, 790 (97.7%) felt that healthcare providers were having a positive attitude towards them. In addition, 772 (95.5%) felt that doctors showed interest in them as a whole. About 320 (79.3%) beneficiaries attending rural HWCs were satisfied with the overall treatment received in comparison with 254 (62.8%) beneficiaries attending urban HWCs. The satisfaction level on the overall treatment received was low among urban HWCs beneficiaries. Conclusions: Majority of the patients were satisfied with the health care services offered at HWCs and healthcare providers at HWCs.